Teaching the Pentateuch: Challenges and Opportunities - Milstein, Sara (Teaching theology and religion, 2025)
What are best practices for teaching the Pentateuch and the Hebrew Bible more broadly? How can we introduce students to ways of reading biblical texts that are eye-opening, empowering, and accessible? In this paper, I explore some of the challenges and opportunities that we face as biblical studies professors, and I profile a handful of examples that have been especially fruitful in my experience teaching undergraduates. On the whole, my approach is text-centered and student-centered. Regarding the former, rather than promoting a one-size-fits-all method, I try to approach each text or set of texts on its/their own terms, asking which method, set of questions, or article will best illuminate it. Regarding the latter, I advocate for pedagogical practices that encourage students to reach conclusions on their own, especially when it comes to complex questions pertaining to the development of texts over time. Finally, I believe that we must make our syllabi, exams, and research more diverse and inclusive if we want the field to thrive and if we want more students to have “a place at the table” in the years to come.